Lipohypertrophy contributing to severe diabetic ketoacidosis in type 1 diabetes: An increasing problem in the context of the COVID‐19 pandemic? - Emilia Imogen Smith; Andra Ciutac; Jamie C. Smith (Clinical Case Reports, 2022)
Abstract A 57‐year‐old man with type 1 diabetes was admitted with diabetic ketoacidosis during the COVID‐19 pandemic. On examination, there was evidence of severe lipohypertrophy on his abdomen. Repeated injection of subcutaneous insulin into areas of lipohypertrophy was thought to have contributed to the development of ketoacidosis.